2023
DOI: 10.1177/22785337221148841
|View full text |Cite
|
Sign up to set email alerts
|

Reconnoitering the Effects of Risk and Knowledge on Use Intention for E-money Services Among Saudi Arabian Residents

Abstract: Technology impacts human life in multiple ways, and the internet offers the facility to perform traditional money transactions instantly. However, technology adoption is risky, and numerous risks hinder the intention formation from using e-money services. The current work investigates four types of associated risks (financial, service, time, and psychological risk) impacting the use intention for e-money services among Saudi Arabian and estimating the effect of e-money services knowledge on the use intention. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 42 publications
0
3
1
Order By: Relevance
“…Öztürk (2022) also reported a significant relationship between psychological risk and attitudes towards halal products. However, these findings contrast with those by Salameh et al (2024) and Zhu et al (2022), who found no significant relationship between psychological risk and the intentions to use e-money services and mobile payments, respectively, among Thai consumers. These mixed results underscore the importance of addressing psychological barriers to enhance the acceptance of mobile payment systems.…”
Section: Resultscontrasting
confidence: 97%
See 3 more Smart Citations
“…Öztürk (2022) also reported a significant relationship between psychological risk and attitudes towards halal products. However, these findings contrast with those by Salameh et al (2024) and Zhu et al (2022), who found no significant relationship between psychological risk and the intentions to use e-money services and mobile payments, respectively, among Thai consumers. These mixed results underscore the importance of addressing psychological barriers to enhance the acceptance of mobile payment systems.…”
Section: Resultscontrasting
confidence: 97%
“…These findings align with those of Yang et al (2015) and Masoud (2013), who observed no significant impact of time risk on the intentions to use mobile payments and online shopping, respectively. Similarly, Salameh et al (2024) found no significant relationship between time risk and the intention to use e-money services. However, this study's results contrast with those of Almousa (2011), Zhu et al (2022), and Munikrishnan et al (2023, who identified a significant influence of time risk on online shopping and mobile payment attitudes.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations